Club foot in association with the 22q11.2 deletion syndrome: An observational study. Issue 10 (31st October 2018) - Homans, Jelle F.; Crowley, Terrence B.; Chen, Erin; McGinn, Daniel E.; Deeney, Vincent F. X.; Sakkers, Ralph J. B.; Davidson, Richard S.; Castelein, René M.; McDonald‐McGinn, Donna M.
Abstract : The 22q11.2 Deletion Syndrome (22q11.2DS) occurs in 1:3, 000–6, 000 individuals. Features less typically associated with 22q11.2DS, such as orthopedic manifestations, may be overlooked or may not lead to appropriate diagnostic testing. Club foot has a general population prevalence of 1:1, 000 and has been occasionally described in association with 22q11.2DS. Our hypothesis is that the prevalence of club foot is higher in patients with 22q11.2DS. We performed a retrospective review in two specialized 22q11.2DS centers to determine the prevalence of club foot. "True club foot" requires treatment (either conservative or surgical), therefore we only included those patients with proof of treatment. We investigated whether congenital heart disease (CHD) and/or cleft palate were associated with the presence of club foot within 22q11.2DS. The records of 1, 466 patients were reviewed. Of these, 48 (3.3%) had confirmation of club foot (95% Confidence Interval: 2.4–4.3): 22 (46%) had a bilateral, 12 (25%) left, and 14 (29%) right club foot. Within our study, neither a CHD and/or a cleft palate were associated with a club foot. The prevalence of club foot in 22q11.2DS is 30 times higher than that observed in the general population. This suggests the diagnosis of club foot, especially in the face of other typically associated abnormalities of 22q11.2DS, should provoke consideration of 22q11.2DS as an underlying diagnosis, particularly in the neonatal setting.